1997
DOI: 10.1021/bi970185v
|View full text |Cite
|
Sign up to set email alerts
|

Thymosin β4 Binds Actin in an Extended Conformation and Contacts both the Barbed and Pointed Ends

Abstract: The beta-thymosins are a family of highly polar peptides which serve in vivo to maintain a reservoir of unpolymerized actin monomers. In vitro, beta-thymosins form 1:1 complexes with actin monomers and inhibit both polymerization and exchange of the bound nucleotide. Circular dichroism data indicate that free thymosin beta 4 is predominantly unstructured, containing at most six residues of alpha-helix, and that up to six additional residues may adopt an alpha-helical conformation upon binding actin. NMR data i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
106
0

Year Published

1997
1997
2016
2016

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 110 publications
(116 citation statements)
references
References 54 publications
10
106
0
Order By: Relevance
“…These results imply that, in agreement with results of Safer et al (12) and De La Cruz et al (13), the C terminus of thymosin ␤ 4 likely contributes to the binding of the intact protein by direct interactions with actin. It is unlikely that the 5 residues N-terminal to our peptide are responsible for binding of intact thymosin ␤ 4 to actin in the presence of the peptide because others have shown that these residues are not important in this regard (9).…”
Section: Steadysupporting
confidence: 90%
See 1 more Smart Citation
“…These results imply that, in agreement with results of Safer et al (12) and De La Cruz et al (13), the C terminus of thymosin ␤ 4 likely contributes to the binding of the intact protein by direct interactions with actin. It is unlikely that the 5 residues N-terminal to our peptide are responsible for binding of intact thymosin ␤ 4 to actin in the presence of the peptide because others have shown that these residues are not important in this regard (9).…”
Section: Steadysupporting
confidence: 90%
“…Also, this assumption has been used as the basis for the analysis of data concerning putative functions of profilin other than monomer sequestration (5,6,11). However, the recent evidence that the surface of interaction between thymosin ␤ 4 and actin is extensive, involving both subdomains 1 and 2 of actin (12,13), implies that there is no structural basis for competitive binding between these actinbinding proteins, and has lead us to re-investigate the hypothesis that profilin and thymosin ␤ 4 could form a ternary complex with actin. Additional support for this hypothesis is provided by data showing that some variations in the C terminus of thymosin ␤ 4 alter actin affinity and explain, in part, the differences in actin binding activity of ␤-thymosin isoforms (14,15).…”
mentioning
confidence: 99%
“…(C) Same experiment as in A and B, but using tetraThymosin␤ mutant tT␤R 1,2,4 that is mers simultaneously, most probably via repeats 1, 2, and 4. Similar to thymosin␤4 (Safer et al, 1997), tetraThymosin␤ likely adopts an extended conformation (it is largely unstructured as a free protein, our unpublished results) enabling the formation of complexes with varying stoichiometry. Analogously to our results, actobindin is shown to contain two functional actin-binding modules (Vancompernolle et al, 1991) and to complex an actin dimer (Bubb et al, 1994).…”
Section: Discussionmentioning
confidence: 93%
“…10 Tissue was desegregated and diluted up to 150 g/mL total protein with cold phosphate-saline buffer; 100-L aliquots of the homogenate were incubated at 37°C with: (1) Safer, University of Pennsylvania, Philadelphia, Pa), 20 was dissolved in water. Three different POPi were used: Z-prolyl-prolinal (Z-ProPro, Biomol), Fmoc-prolyl-pyrrolidine-2-nitrile (Fmoc-Pro-PyrrCN, a gift of S. Wilk, Mount Sinai School of Medicine, NY), 21 and S17092 (a gift of P. Vanhoutte, Institut de Recherches Internationales Servier, France).…”
Section: Effect Of Popi On Ac-sdkp Synthesis In Vitromentioning
confidence: 99%